Study of Magnetoacoustic solitons in ultra dense quantum electron-positron-ion plasma (Latakia University Journal -Basic Sciences Series, 2019)
In this search, it has been studied the properties  of the  magnetoacoustic soliton waves in ultra dense quantum plasma and its including  ions and electrons and positrons after taking quantum  effects of electrons and positrons into consideration due to their Fermionic nature and the quantum diffraction, this is  by the quantum Bom potential into two momentum equations of electrons and positrons .It has been studied the solitary  waves of small amplitude by using reductive perturbation method. The results have been compared to the solitary waves ones with what others have reached in related references.